Aspectos de la concordancia de número en las lenguas eslavas - Benitez Burraco, antonio (Eslavística Complutense, 2007)
Agreement in number depends mainly on syntactic factors, but also semantic and/or pragmatic ones seem to be relevant. Among Slavonic languages, canonical instances of agreement are predominant. Nevertheless, conflicting agreements also appear, when both semantic and syntactic agreements are possible (semantic plausibility is also relevant in some cases). Both synchronic and diachronic aspects concerning agreement in number among Slavonic languages will be discussed in this paper. Number resolution rules (when conflicts arise) will be also considered.